2020
DOI: 10.1177/0146167220949362
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change in Personality Traits and Major Life Goals From College to Midlife

Abstract: The association between personality traits and motivational units, such as life goals, has been a long-standing interest of personality scientists. However, little research has investigated the longitudinal associations between traits and life goals beyond young adulthood. In the present study ( N = 251), we examined the rank-order stability of, and mean-level changes in, the Big Five and major life goals (Aesthetic, Economic, Family/Relationship, Hedonistic, Political, Religious, Social) from college (age 18)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 50 publications
12
80
1
2
Order By: Relevance
“…Hudson et al (2019) found that people can change their personality when they have the desire to change and actively pursue the goal of change. Similarly, Atherton et al (2021) found co-development of personality and life goals, concluding that individuals self-regulate by formulating goals that are consistent with their personality traits. Conversely, placing importance on cer tain goals promotes changes in corresponding traits, presumably because investing in goal-relevant contexts places rewards, punishments, and contingencies on certain traits.…”
Section: What Directions Should Research On Self Andmentioning
confidence: 88%
“…Hudson et al (2019) found that people can change their personality when they have the desire to change and actively pursue the goal of change. Similarly, Atherton et al (2021) found co-development of personality and life goals, concluding that individuals self-regulate by formulating goals that are consistent with their personality traits. Conversely, placing importance on cer tain goals promotes changes in corresponding traits, presumably because investing in goal-relevant contexts places rewards, punishments, and contingencies on certain traits.…”
Section: What Directions Should Research On Self Andmentioning
confidence: 88%
“…We know far less about longitudinal changes in social and emotional skills. Measures of motivation, when assessed as the importance or salience of a goal show a very consistent pattern of no mean-level change or decreasing across the life course (Atherton, Grijalva, Roberts, & Robins, 2020;Stoll, Rieger, Nagengast, Trautwein, & Rounds, 2020). When measured as interests, the picture for motivation grows more complex, possibly as a result of having fewer long-term studies in adulthood.…”
Section: Personality Developmentmentioning
confidence: 99%
“…To the extent that vocational interests are exemplary constructs in the motivation domain, we know that they are actually more consistent than personality traits at a younger age (Low et al, 2005) and show similarly high levels of consistency over decades (Nye, Willie, Amory, & De Fruyt, 2020;Schultz, Connolly, Garrison, Leveille, & Jackson, 2017). Though less often studied, other motivational constructs, such as major life goals (Atherton et al, 2020) and values (Dobewall & Aavik, 2016;Vecchione et al, 2016) are as consistent as personality traits over comparable time intervals. Skills, at least in terms of the traditional measures of cognitive ability, appear to be more consistent than any other domain in personality (Deary, Whiteman, Starr, Whalley, & Fox, 2004;Tucker-Drob & Briley, 2014) with estimates of consistency exceeding .80 for samples older than 20.…”
Section: Personality Developmentmentioning
confidence: 99%
“…The accompanying shift toward interpersonal harmony and maturity is seen across a variety of traits that share some empirical overlap with the BAP (Lamport & Turner, 2014;Wainer et al, 2011). For example, people tend to become more agreeable, conscientious, empathetic, and secure in their relationships while also declining in neuroticism and social anxiety over time (Atherton et al, 2020;Oh et al, 2019). Such changes in prosocial traits and characteristics likely have implications for the BAP.…”
Section: The Bap Across the Lifespanmentioning
confidence: 99%